2023
DOI: 10.3389/fonc.2022.960116
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Pharmacokinetics of pembrolizumab in a patient with stage IV non–small cell lung cancer after a single 200 mg administration

Abstract: BackgroundPembrolizumab is a well-tolerated biologic agent with a potentially stable and durable anti-tumor response. Unfortunately, discontinuation of therapy can occur as a consequence of immune-related adverse effects (irAEs). These irAEs appear independent of dose and exposure. However, such irAEs might also result from pembrolizumab’s highly specific mechanism of action and current dosing regimens. However, the currently available pharmacokinetic (PK) and pharmacodynamic (PD) data to reassess dosing strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Therefore, a regimen of 1 mg/kg every 3 weeks (minimum C, SS, 12.8 µg/mL) versus a regimen of 2 mg/kg every 3 weeks (minimum C, SS, 25.5 μg/mL) can reasonably be expected to result in only a modest reduction in activity. In addition, it was noted that no difference in the exposure–response relationship was observed between doses of 1 to 10 mg/kg and therefore it was suggested that a regimen of 1 mg/kg every 3 weeks might be sufficient to achieve clinical efficacy [ 21 ].…”
Section: Pharmacokinetic and Pharmacodynamic Rationalementioning
confidence: 99%
“…Therefore, a regimen of 1 mg/kg every 3 weeks (minimum C, SS, 12.8 µg/mL) versus a regimen of 2 mg/kg every 3 weeks (minimum C, SS, 25.5 μg/mL) can reasonably be expected to result in only a modest reduction in activity. In addition, it was noted that no difference in the exposure–response relationship was observed between doses of 1 to 10 mg/kg and therefore it was suggested that a regimen of 1 mg/kg every 3 weeks might be sufficient to achieve clinical efficacy [ 21 ].…”
Section: Pharmacokinetic and Pharmacodynamic Rationalementioning
confidence: 99%